The government transformation programme of Malaysia: a successful approach to public service reform - Xavier, John Antony; Siddiquee, Noore Alam; Mohamed, Mohd Zin (Routledge, 2016)
The 2009 Malaysian Government Transformation Programme (GTP) could be useful as a model for reform given its positive impact on improving public services in targeted key result areas. This paper assesses the GTP's approach in the context of the wider debate on whether reforms should be based on best practices or whether they should be diagnostic or problem-solving in approach. The GTP's success was largely the result of blending both approaches. The GTP experience in Malaysia provides a number of insights and lessons for delivering intelligent reforms quickly and effectively.